2019
DOI: 10.1177/0894845319837374
|View full text |Cite
|
Sign up to set email alerts
|

Combating Burnout by Increasing Job Relational Characteristics

Abstract: The current study developed and tested the indirect effect of the relational job characteristics (i.e., perceived prosocial impact and perceived social value) on the burnout syndrome through the autonomous motivation. The cross-sectional survey data analysis of 1,538 Portuguese contact center workers was analyzed using the software package Mplus to conduct structural equation models. Autonomous motivation partially explains the negative relation between the relational job characteristics and burnout. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Secondly, the perceived overqualification contributes to more controlled motivation for having a contact center job, which results from the worker's perception that this job does not permit that he or she uses his/her competencies and skills (Fine, 2007). Thus, organizations should re-design the contact center work and promote task variety, autonomy, and workers' participation (Castanheira and Chambel, 2010) and relational job characteristics (Gonçalves et al, 2019). Finally, the organizations should promote the workers' proactivity because the workers that perceive higher overqualification should be predisposed to modify their work (job crafting) to make it more stimulating (Wrzesniewski et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the perceived overqualification contributes to more controlled motivation for having a contact center job, which results from the worker's perception that this job does not permit that he or she uses his/her competencies and skills (Fine, 2007). Thus, organizations should re-design the contact center work and promote task variety, autonomy, and workers' participation (Castanheira and Chambel, 2010) and relational job characteristics (Gonçalves et al, 2019). Finally, the organizations should promote the workers' proactivity because the workers that perceive higher overqualification should be predisposed to modify their work (job crafting) to make it more stimulating (Wrzesniewski et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, they have analyzed staff members of a US university and professors from Spain, respectively, and with the current research, we will focus on Portuguese contact center workers. Burnout is an unpleasant condition that is detrimental for both individuals and organizations and is a well-known problem within the contact center work setting (Srivastava and Dey, 2020;Gonçalves et al, 2019). Thus, studies like the current one, analyzing burnout predictors could offer an important contribution to the literature (Gonçalves et al, 2019).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The role of mindfulness and emotional intelligence that is considered the motivational aspect of a sense of coherence represents how beliefs and the extent to which individuals want to overcome them based on the belief that they have sufficient resources to successfully face guidance so that this motivation can give contact center employees encouragement to participate more in delivering results, thus creating a sense of mindfulness in their work. Gonçalves et al (2020) emphasizes research on internal or intrinsic motivation on the aspects of autonomous motivation and relational job caracteristic (RJC) to burnout. The results showed that the presence of certain RJCs in the contact center (i.e., perceived social values and perceived prosocial impacts)…”
Section: Resultsmentioning
confidence: 99%
“…The entire study is a quantitative description study and uses sampling techniques of nonprobabability sampling. The measuring instrument used in all studies used the Maslach Burnout Inventory (MBI) questionnaire (Geraldes et al, 2019;Gonçalves et al, 2020;Dwi Lestari & Yuwono, 2020;Montalbo, 2016;Drissi et al, 2021;Charoensukmongkol & Puyod, 2020;Harry, 2021;Deniz & Kaya, 2021). Kuesione is distributed in person as well as online.…”
Section: Methodsmentioning
confidence: 99%